2021
DOI: 10.1177/0030222821993624
|View full text |Cite
|
Sign up to set email alerts
|

“I Don’t Know What to Say”: Teachers’ Perspectives on Supporting Bereaved Students After the Death of a Parent

Abstract: This qualitative study examined teachers’ experiences dealing with bereaved students following the death of a parent. The researchers conducted in-depth, semi-structured, face-to-face interviews with 25 teachers in Israeli schools who had counseled one of their students after the death of a parent. The interviews were recorded and transcribed and underwent content analysis. Analysis of the findings revealed that the teachers felt helpless, confused, overloaded emotionally and anxious when counseling students w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“…[5][6][7] These studies also highlight the discomfort that educators often feel in conversations with grieving students and have identified a lack of training, uncertainty about what to say or avoid saying, and awareness of their own emotions around grief and loss as root causes of that discomfort. [5][6][7][8] Many of these studies have identified formal grief-sensitive training as a potential solution. 5,6,8 Interestingly, participants in a 2020 study by Case et al who had some previous exposure to coursework on grief sensitivity continued to feel unprepared to engage grieving students because they felt this coursework did not prepare them for how they would react in specific situations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[5][6][7] These studies also highlight the discomfort that educators often feel in conversations with grieving students and have identified a lack of training, uncertainty about what to say or avoid saying, and awareness of their own emotions around grief and loss as root causes of that discomfort. [5][6][7][8] Many of these studies have identified formal grief-sensitive training as a potential solution. 5,6,8 Interestingly, participants in a 2020 study by Case et al who had some previous exposure to coursework on grief sensitivity continued to feel unprepared to engage grieving students because they felt this coursework did not prepare them for how they would react in specific situations.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has explored the emotional experience of educators while supporting grieving students, noted the potential for emotional distress in these endeavors, and advocated for programs to support educators in processing the emotions that might arise. 8 Emerging research since the COVID-19 pandemic has also noted increased stress, compassion fatigue, and burnout in educators. [10][11][12] Increased isolation, a significant increase in mandatory new procedures and professional development related to the pandemic, converting to online instruction, and returning to in-person instruction have been highlighted as factors related to educator stress and burnout.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of schools as a significant support factor in the lives of bereaved children has been established in a range of studies (Dyregrov & Dyregrov, 2008;Holland, 2008;Lytje, 2017). While some studies (Lytje, 2018b;Tracey, 2011) have found that children generally welcome such support, other studies (eg Holland, 2008;Levkovich & Elyoseph, 2021) have shown that many teachers do not feel adequately trained to handle bereavement. Holland (2001) reported that British teachers were generally wary of engaging with bereaved children, as they were worried about 'causing an upset' (p 121).…”
Section: Risk and Protective Factorsmentioning
confidence: 99%
“…Several studies found that school counsellors are responsible for creating an educational space where these children can feel they legitimately belong and can openly and honestly express their opinions and emotions (Brown, 2020; Brown & Barrio, 2017; Levkovich, & Elyoseph, 2021; Lopez & Burt, 2013). School counsellors are entrusted with collecting information on the life reality of students with an incarcerated parent and with updating the homeroom teachers (Petsch & Rochlen, 2009).…”
Section: Introductionmentioning
confidence: 99%